2008
DOI: 10.1152/ajpgi.00470.2007
|View full text |Cite
|
Sign up to set email alerts
|

Manometric evidence for a phonation-induced UES contractile reflex

Abstract: The mechanism against entry of gastric content into the pharynx during high-intensity vocalization such as seen among professional singers is not known. We hypothesized that phonation-induced upper esophageal sphincter (UES) contraction enhances the pressure barrier against entry of gastroesophageal contents into pharynx. To determine and compare the effect of phonation on luminal pressures of the esophagus and its sphincters, we studied 17 healthy volunteers (7 male, 10 female) by concurrent high-resolution m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 35 publications
1
19
3
Order By: Relevance
“…the cough refl ex. Similar to our previous reports in healthy young and elderly subjects during phonation events, 27,28 this fi nding suggests the presence of a UES contractile response as part of the cough refl ex. To further support this notion, there is electromyographic evidence of contraction of the cricopharyngeus muscle during cough in animal models.…”
Section: Interobserver Agreementsupporting
confidence: 91%
“…the cough refl ex. Similar to our previous reports in healthy young and elderly subjects during phonation events, 27,28 this fi nding suggests the presence of a UES contractile response as part of the cough refl ex. To further support this notion, there is electromyographic evidence of contraction of the cricopharyngeus muscle during cough in animal models.…”
Section: Interobserver Agreementsupporting
confidence: 91%
“…The upper esophageal sphincter functions as a gateway within the upper aerodigestive tract. Its resting muscle tone serves critical functions to regulate the opening of the esophagus for swallowing and belching, and protects the airways from invasion of gastric or esophageal contents . Furthermore, upper esophageal sphincter contraction provides post‐swallowing pressures against the tail of the bolus being swallowed to facilitate clearance into the cervical esophagus.…”
Section: Introductionmentioning
confidence: 99%
“…Its resting muscle tone serves critical functions to regulate the opening of the esophagus for swallowing and belching, [1][2][3][4] and protects the airways from invasion of gastric or esophageal contents. [5][6][7][8] Furthermore, upper esophageal sphincter contraction provides post-swallowing pressures against the tail of the bolus being swallowed to facilitate clearance into the cervical esophagus. The cricopharyngeus muscle together with the inferior constrictor and cervical esophageal fibers comprise the upper esophageal sphincter.…”
Section: Introductionmentioning
confidence: 99%
“…The increased pressure in the UES could be due to a mechanical squeeze of the sphincter and the pharynx. It is hypothesized that this squeeze is caused by surrounding structures, such as posterior movement of the larynx pressing the sphincter and the hypopharynx against the spine due to increased (para)laryngeal muscle tension [5]. To what extent manometric recordings can document the diagnosis of MTD is worthwhile investigating.…”
mentioning
confidence: 99%
“…To what extent manometric recordings can document the diagnosis of MTD is worthwhile investigating. Previous research with manometry by Perera et al [5] showed that phonation in normal speakers was associated with a different magnitude of increase in intraluminal pressure in the UES, esophagus, and lower esophageal sphincter (LES). This phenomenon was observed for both high and low pitch.…”
mentioning
confidence: 99%